Projection of urban expansion and related changes in soil carbon stocks in the Moscow Region. (1st January 2018) - Vasenev, V.I.; Stoorvogel, J.J.; Leemans, R.; Valentini, R.; Hajiaghayeva, R.A.
Abstract: Urbanization is responsible for large environmental changes worldwide. Although traditionally urbanization was related to negative environmental impacts, recent research also highlights positive impacts like the potential of urban areas to store soil organic carbon. The net effect of urbanization on soil organic carbon is poorly understood. Negative influences of construction and soil sealing may be compensated by the establishment of green areas. Possible net effects of future urbanization on soil organic carbon stocks were explored for the Moscow Region, based on the soil survey and land conversion model. The regional urbanization was modelled as a function of environmental, socio-economic and neighbourhood factors. This yielded three alternative scenarios for urbanization: i) including neighbourhood factors; ii) excluding neighbourhood factors and focusing on environmental drivers; and iii) considering the New Moscow Project that includes the establishment of 1500 km 2 of new urbanized area following governmental regulation. The three scenarios showed substantial expansion of urban areas on 30, 10 and 80%. The model, considering neighbourhood effect was the most accurate with 91% of correct predictions. Urbanization in the region mainly converted forests, fallow and arable lands. The negative effect of urbanization (i.e soil sealing and excavation of topsoil for building construction) was compensated by positive effect (e.i. urban greenery and "cultural layers"). In result an increase of soil organic carbon stocks of 4.2 ± 1.7 to 11.0 ± 2.6 Tg C was shown for all three scenarios. The highest increases in soil organic carbon stocks occurred on the less fertile Orthic Podzols and Eutric Podzoluvisols, whereas SOC stocks in Orthic Luvisols, Luvic Chernozems, Dystric Histosols and Eutric Fluvisols increased less. Subsoil C-stocks were much more affected with an extra 4 ± 1.6 to 10 ± 2.4 Tg soil organic carbon than those in the topsoils. The highest increase of both topsoil and subsoil soil organic carbon stocks occurred in the New Moscow scenario with the highest urbanization. Even when the relatively high uncertainties of the absolute C-stocks are considered, the outcomes highlight the potential of cities to enhance soil organic carbon storage. This will progressively become more important in the future following the increasing world-wide urbanization.